A Nutrition Education Program in Rural Bangladesh Was Associated with Improved Feeding Practices but Not with Child Growth. Issue 5 (15th March 2017) - Owais, Aatekah; Schwartz, Benjamin; Kleinbaum, David G; Suchdev, Parminder S; Faruque, Abu Syed Golam; Das, Sumon K; Rahman, Shahed; Stein, Aryeh D
Abstract: Background: Childhood undernutrition is a major public health problem in Bangladesh. Evaluating child nutrition programs is a priority. Objective: The objective of this study was to evaluate a community-based nutrition education program (implemented from 2011 to 2013) aimed at improving infant and young child feeding (IYCF) practices and growth in rural Bangladesh. Methods: A cohort-based evaluation was conducted that included 2400 women (1200 from Karimganj, the intervention subdistrict, and 1200 from Katiadi, the control subdistrict) enrolled at 28–31 wk gestation in 3 waves between January and October 2011. Follow-up occurred at 3, 9, 16, and 24 mo of offspring age. The main outcomes were exclusive breastfeeding (EBF), measured at 3 mo, timing of complementary feeding (CF) initiation and minimum acceptable diet (MAD), measured at 9 mo, and child growth [assessed via length-for-age z score (LAZ) and weight-for-length z score], measured at all follow-ups. The main exposures were subdistrict of residence and wave of enrollment. For IYCF practices as outcome, logistic regressions were used. Generalized estimating equations were used for child growth as outcome. Results: EBF rates at 3 mo remained unchanged between waves 1 and 3 in Karimganj (55.6% compared with 57.3%), but the proportion of infants receiving timely CF initiation and MAD at 9 mo increased significantly (CF: 27.1–54.7%; MAD: 8.4–35.3%). Mean LAZ at 24 mo remained unchanged between waves 1 and 3 in Karimganj (−2.18 compared with −1.98). Conclusions: The program was successful in improving the quality of infant diet at 9 mo and timely CF initiation, but not EBF at 3 mo or LAZ. These findings support the case for implementing simple messages in all programs aimed at improving infant diet, especially in settings in which supplementing overall household diet may not be feasible.